Chapter 5: The commission of maritime crimes with unmanned systems: an interpretive challenge for the United Nations Convention on the Law of the Sea - Petrig, Anna (Edward Elgar Publishing, 2020)
Over the past decade, two important developments relevant for international maritime security law have taken place: first, the security landscape at sea has changed considerably, with transnational crimes now ranking high on the list of maritime security threats; second, the 'robotics revolution' has reached the sea with the advent of unmanned vehicles. Combined, these developments have led to increased reliance by non-State actors on unmanned systems when committing criminal offences at sea. The use of unmanned systems does not imply that there is no human involvement in the commission of maritime crimes but its nature changes: the offender's involvement is remote rather than proximate in terms of both geography and time. This shift from proximate to remote human involvement shakes the foundation of the provisions of the United Nations Convention on the Law of the Sea (LOSC) relating to crimes at sea, which rest on an assumption of proximity, that is, that the perpetrator is on board the offending craft and in the vicinity of where the harmful act unfolds. This raises the question whether LOSC is capable of accommodating the turn to this transformative technology. It is against this backdrop that this chapter looks at the various mechanisms intended to keep LOSC abreast of change. It concludes that whilst the prevailing strategy - evolutionary interpretation - is generally a suitable method to keep the Convention in tune with the times, this approach is inappropriate for provisions of LOSC relating to the suppression of maritime crime. It is submitted that these provisions, which result from a conjunction between the law of the sea and (transnational) criminal law, must rather be subject to a 'rule of law'-based interpretation. This, however, considerably curtails the available interpretive space and the possibility of accommodating the 'robotics revolution' at sea within Part VII of LOSC.